Refined Quantification of Infection Bottlenecks and Pathogen Dissemination with STAMPR - Karthik Hullahalli (American Society for Microbiology, 2021)
Barcoded bacteria are often employed to monitor pathogen population dynamics during infection. The accuracy of these measurements is diminished by unequal bacterial expansion rates.